Identification of Induction Motor Parameters in Vector Control Electric Drives - Kuznetsov, Vitaliy V.; Tsyplenkov, Dmytro; Nikolenko, Anatoliy V. (ScientificWorld-NetAkhatAV, Karlsruhe, Germany, 2024)
ENG: The paper is devoted to the questions of identifying coordinates and parameters of asynchronous engine and the increase of the quality of electromechanical transition processes of asynchronous electric drive with a vector control at indirect determination.

UKR: Робота присвячена питанням визначення координат і параметрів асинхронного двигуна та підвищення якості електромеханічних перехідних процесів асинхронного електропривода з векторним керуванням при непрямому визначенні.
Ідентифікація параметрів асинсинрового двигуна в електроприводах векторного керування
V. Kuznetsov: ORCID 0000-0002-8169-4598; D. Tsyplenkov: ORCID 0000-0002-0378-5400; A. Nikolenko: ORCID 0000-0003-3808-4249
Keywords: identification; device of observation; tuning coefficients; sample model; asynchronous electric drive; vector control; ідентифікація; прилад спостереження; коефіцієнти налаштування; модель зразка; асинхронний електропривод; векторне керування; КЕЛІ; TECHNOLOGY::Electrical engineering, electronics and photonics::Electrical engineering